The Pentatricopeptide Repeat Protein MEF31 is Required for Editing at Site 581 of the Mitochondrial tatC Transcript and Indirectly Influences Editing at Site 586 of the Same Transcript. (4th December 2017) - Arenas-M, Anita; Gonzlez-Durn, Enrique; Gmez, Isabel; Burger, Matthias; Brennicke, Axel; Takenaka, Mizuki; Jordana, Xavier
Abstract: Pentatricopeptide repeat (PPR) proteins constitute the largest family of proteins in angiosperms, and most members are predicted to play roles in the maturation of organellar RNAs. Here we describe the novel mitochondrial editing factor 31 (MEF31), an E-PPR protein involved in editing at two close sites in the same transcript encoding subunit C of the twin-arginine translocation (tat) pathway. MEF31 is essential for editing at site tatC -581 and application of the recently proposed amino acid code for RNA recognition by PPR proteins supports the view that MEF31 directly targets this site by recognizing its cis sequence. In contrast, editing at site tatC -586 five nucleotides downstream is only partially affected in plants lacking MEF31, being restored to wild-type levels in complemented plants. Application of the amino acid code and analysis of individual RNA molecules for editing at sites 581 and 586 suggest that MEF31 does not directly target site tatC -586, and only indirectly influences editing at this site. It is likely that editing at site tatC -581 improves recognition of the site tatC -586 cis sequence by a second unknown PPR protein.